2014
DOI: 10.1111/dmcn.12665
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study investigating gross motor function, pain, and health‐related quality of life 17 years after selective dorsal rhizotomy in cerebral palsy

Abstract: ROMRange of motion SDR Selective dorsal rhizotomy AIM The aim of this study is to evaluate the long-term effects of selective dorsal rhizotomy (SDR), 15 to 20 years after surgery in patients with cerebral palsy.METHOD Eighteen children (four females, 14 males; mean age at SDR 4y 7mo, SD 1y 7mo) with bilateral spastic cerebral palsy (CP), were prospectively assessed after SDR. This study focuses on the outcome 15 to 20 years after the procedure. The assessments include the Modified Ashworth Scale for spasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 32 publications
4
92
1
2
Order By: Relevance
“…Our study participants reported that pain caused only a minimal interference with activities. Tedroff et al reported similar results, but, owing to lack of a control group, concluded this benefit may be due to the SDR . Our study suggests alternative treatment regimens equally prevent the onset of pain through early adulthood.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our study participants reported that pain caused only a minimal interference with activities. Tedroff et al reported similar results, but, owing to lack of a control group, concluded this benefit may be due to the SDR . Our study suggests alternative treatment regimens equally prevent the onset of pain through early adulthood.…”
Section: Discussionsupporting
confidence: 65%
“…Long‐term studies up to 26 years post‐SDR suggest that many important outcomes peak 1 to 3 years after surgery . This peak has been shown for gross motor function (Gross Motor Function Measure), ambulatory status (Wilson Mobility Scale), ankle ROM, and popliteal angle.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the fact that many children with spastic CP eventually develop skeletal muscle contractures, spasticity has been believed to be causative and clinical practice has up until recently been focused on spasticity reducing therapies for the preservation of motor function. However, recent reports have clearly demonstrated that despite good control of spasticity and reduction of muscle tone, by intramuscular botulinum toxin injections (chemical denervation) or selective dorsal rhizotomy that disrupts the reflex loop, skeletal muscle contracture formation progresses (Alhusaini et al, 2011; Tedroff et al, 2014). The poor effect of spasticity reduction on contracture development has raised the question of whether other factors such as growth disturbances and/or alterations in muscle composition are of greater mechanistic importance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reports that spasticity was found only minimally relates to gross motor function in children with bilateral CP [10]. Likewise, studies evaluating gross motor function before and after muscle tone reduction have shown no or limited functional gains despite spasticity reduction [11, 12]. In a previous study, we found that neither spasticity nor contractures could determine the need for support to stand in children with bilateral CP [4].…”
Section: Introductionmentioning
confidence: 84%